The Middle Niger Basin in Nigeria Has a Rift Origin, as Revealed by the Inversion and Modeling of Gravity and Magnetic Data - Salawu, Naheem Banji; Omosanya, Kamaldeen Olakunle L.; Fournier, Dominique (Earth and space science (Hoboken, N.J.), 2024)
The NW‐SE oriented Middle Niger Basin, which is a Campano‐Maastrichtian inland basin has been the subject of debate among geoscientists regarding its origin and development. This paper aims to unravel the basin's origin and evolution by using high‐resolution magnetic, gravity, and topographical data. The integration of aeromagnetic and gravity data provides a means to assess the influence of igneous intrusions during the basin's evolution. The study presents a new perspective on the origin of the basin, suggesting a rift origin where orthogonal extension played a crucial role in its evolution. The research also investigates the relationship between intrusive rocks and the formation of the basin, finding these rocks are solely located within the basement. The magnetic and gravity maps reveal anomalies associated with intrusive structures within the Precambrian crystalline basement. This is a common feature shared with rifted basins on a global scale. Plain Language Summary The Middle Niger Basin, which spans about 350 km from Dekina in the SE to Shegwa in the NW, is unique among Nigerian basins due to the absence of a universally accepted description of its evolution within the geoscientific community. Magnetic data analysis reveals circular and elliptical anomalies that correspond to intrusive rocks. These anomalies are further enhanced by 2‐D forward modeling and gravity data inversion. Additionally, the SRTM data identifies lineaments that border the rifted basin, supporting the interpretations from the magnetic and gravity data. Our study suggests that fractures facilitated igneous intrusions, shaping the basin's evolution and providing new insights into its tectonic history. The new findings from this research provide valuable insights into the evolution of the Middle Niger Basin and may serve as a useful guide for future exploration initiatives. Key Points The axis of the Middle Niger Basin is marked by structural discontinuities Intrusions in the basement of the basin were constrained by gravity inversion Evolution of the Middle Niger Basin is primarily controlled by crustal extension